Sustainable Aquaculture Ecosystem Solutions In E-Commerce Business - Rifainy, Amnila Hanisah; Mostar, Jovito Benhart Ramadhan; Maulana, Rizkian; Yudawisastra, Helin G (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
Indonesia is a maritime archipelagic country with vast territorial waters. Currently, food security is a severe problem in the world. In 2020, after the COVID-19 pandemic, 811 million people experienced hunger problems. It is estimated that in 2030 this number will be higher and become a global problem. One of the opportunities to increase the amount of food production for food sufficiency is through aquaculture. Advances in technology and telecommunications support the development of online-based businesses such as e-commerce. By using e-commerce, manufacturers can market various products or services worldwide. This study aims to describe aquaculture solutions in the e-commerce business in Indonesia. The object of the research is eFishery, which is the first aquatech e-commerce company in Asia. This research method is exploratory with a prospective case study. Data collection techniques are primary data in the form of interviews and secondary data in the form of observation. The research results are expected to be a recommendation for companies and academics concerned about the development of e-commerce business and a reference for action research for further research.